Double Bolus Application in TWIST-MR-Angiography of the Cervical Arteries - Andreas Korn; Michael Fenchel; Till-Karsten Hauser; Sotirios Bisdas; Thomas Nägele; Ulrike Ernemann; Uwe Klose; Benjamin Bender (Radiology Research and Practice)
Purpose. The aim of the present work was to test the feasibility of the time-resolved MR-angiography (TWIST-MRA) of cervical arteries using double bolus injection. Material and Methods. TWIST-MRA with a temporal resolution of 8.4 seconds for each frame and a spatial resolution with a voxel size of was performed in 24 patients. A biphasic bolus injection protocol was used with the second injection being started 21 seconds after the first contrast dye bolus. Diagnostic image quality was rated according to a 4-point scale. Results. In 12 patients (50%) no clear separation between the cervical venous and arterial vessels was evident after the first bolus injection. Using TWIST-MRA data acquired after the second bolus a sufficient diagnostic image quality (rating , mean 3.5) could be obtained in 22 of 24 patients (92%). Discussion. The double bolus injection protocol using TWIST-MRA allows for very good separation of the cervical arteries.